Significant transcriptomic changes are associated with differentiation of bone marrow-derived mesenchymal stem cells into neural progenitor-like cells in the presence of bFGF and EGF - Khan, A.A. (BioMed Central Ltd, 2021)
10.1186/s13578-020-00487-z